A First Step Up the Energy Ladder? Low Cost Solar Kits and Household's Welfare in Rural Rwanda - Michael Grimm; Anicet Munyehirwe; Jörg Peters; Maximiliane Sievert (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2015)
More than 1.3 billion people in developing countries are lacking access to electricity. Based on the assumption that electricity is a prerequisite for human development, the United Nations initiative Sustainable Energy for All (SE4All) has proclaimed the goal of providing modern energy to all by 2030. In recent years, Pico-Photovoltaic kits have become a lower-cost alternative to investment-intensive grid electrification. Using a randomized controlled trial we examine uptake and impacts of a simple Pico-Photovoltaic kit that barely exceeds the benchmark of what the UN considers as modern energy. We find significant effects on households' budget, productivity and convenience. Despite these effects, the data shows that adoption will be impeded by affordability, suggesting that policy would have to consider more direct promotion strategies such as subsidies or financing schemes to reach the UN goal.
Keywords: O13; O18; Q41; D13; I31; 330; energy access; household productivity; household technology adoption; Sub-Saharan Africa; Randomized Controlled Trial